2008
DOI: 10.1590/s0102-09352008000300029
|View full text |Cite
|
Sign up to set email alerts
|

Utilização de ácidos orgânicos e fitase em dietas para leitões na creche

Abstract: RESUMOVerificou-se o efeito da inclusão de um complexo de ácidos orgânicos (AO) e diferentes níveis de fitase em dietas de leitões na creche. Foram utilizados 40 leitões desmamados (7,8±0,8kg), distribuídos em delineamento de blocos inteiramente ao acaso, com cinco tratamentos e quatro repetições, durante um período experimental de 28 dias. Os tratamentos foram: T1-ração basal com 500UF/kg (controle); T2-ração basal com 500UF/kg + 0,2% do complexo de AO; T3-ração basal com 450UF/kg + 0,2% do complexo de AO; T4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…Thus, the lack of effect of the acids in the diets may have occurred due to the highly sanitary conditions of the experimental assays. According to Rocha et al (2008), there may be large variability among piglets in the post-weaning stages, with some animals exhibiting more resistance than others, which makes the fecal score results difficult to interpret. Freitas et al (2006) reported a superior consistency of feces from piglets at 21-49 days of age when organic acids were used in the diet.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the lack of effect of the acids in the diets may have occurred due to the highly sanitary conditions of the experimental assays. According to Rocha et al (2008), there may be large variability among piglets in the post-weaning stages, with some animals exhibiting more resistance than others, which makes the fecal score results difficult to interpret. Freitas et al (2006) reported a superior consistency of feces from piglets at 21-49 days of age when organic acids were used in the diet.…”
Section: Resultsmentioning
confidence: 99%
“…Because organic acids are known to acidify the diet, if the pH of the digesta is reduced, the efficiency of phytase can be improved with the addition of these acids (ROCHA et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, SB may have acted to reduce the intestinal pH. According to Rocha et al (2008), who tested the efficiency of the use of organic acid in nursery piglets, the lower incidence of diarrhoea may be linked to a greater nutrient digestibility caused by enhanced enzyme activity or protein hydrolysis, resulting from a reduction in the pH of the gastrointestinal tract.…”
Section: Incidence Of Diarrhoeamentioning
confidence: 99%